Anchor and chain damage to seafloor habitats in Antarctica: first observations - Mulrennan, Matthew; Graham, Myrah; Herbig, Jennifer; Watson, Sally J. (Frontiers in Conservation Science, 2025)
The number of ships visiting Antarctic waters is increasing. However, the ecological consequences of this increase to Antarctic marine ecosystems remain unclear, including impacts to the seafloor. Benthic and mesopelagic exploratory surveys were conducted in Antarctica in 2022–2023 using deep-sea cameras tethered to a tourism vessel during routine tourism operations. The study area encompassed the Antarctic Peninsula, Weddell Sea, South Shetland Islands, Marguerite Bay, and South Georgia Island. A total of 36 surveys were completed resulting in 62 hours of 4K underwater video footage taken while at anchor or drifting. At Yankee Harbour, the researchers documented anchor and chain damage to sponge colonies, with clear scour marks delineating the disrupted substrate from undisturbed seafloor supporting marine life. Also observed was deposited mud, likely resulting from anchor or chain retrieval. This study presents the first published observation of anchor damage in Antarctica. Despite the observed damage, the Yankee Harbour survey also revealed rich biodiversity in proximity to the impacted areas. Most notably, three large (1–2 meters in height) giant volcano sponges (Anoxycalyx joubini) were observed. This paper shows observations of anchor and chain damage to vulnerable Antarctic seafloor marine life, discusses the potential ecological impacts of anchoring in polar habitats, and provides recommendations to better understand and mitigate further harm.